The relevance of implementing a Bachelor of Arts in English with Specialization in Translation, Interpretation, or Tourism in the Foreign Language Department of the University of El Salvador - Segura Osorio,Wilson Ernesto
The University of El Salvador through the Foreign Language Department is currently offering to the Salvadoran society two Bachelor degrees, these are the Bachelor of Arts in English with Emphasis in Teaching, and the Bachelor of Arts in Modern Languages with Especialization in English and French. Despite the fact that the Bachelor of Arts in English with Emphasis in Teaching has a great demand every year, it is also important to mention that some of the students opt to specialize themselves in other areas of the English language because they do not have other options. In that sense, the present study attempted to reach if the implementation of a new Bachelor of Arts in English is necessary to prepare future professionals in areas such as Translation, Interpretation or Tourism. This research was also motivated to help future professionals to fulfil the demands of companies looking for professionals in those areas in the current labor market as well as to discover the labor necessities of future professional of the current Bachelor of Arts in English with Emphasis in Teaching. The instruments to collect the data involved interviews and surveys administered to recruitment specialists of companies that offer English services to their customers in other countries, and students of the Bachelor of Arts in English with Emphasis in Teaching who were coursing the fifth year during the semester II2019. In addition, the results suggested that even though most of the students agreed with the current Bachelor they were studying, there were many students that were interested in specializations such as translation, interpretation, or tourism. Besides, this research pretends to make a contribution for the improvement and the diversification of the specializations in the Department of Foreign Languages of the University of El Salvador.